Constitutive modeling of cellular-structured metals produced by additive manufacturing. (December 2022) - Kwon, Jihye; Karthik, G.M.; Estrin, Yuri; Kim, Hyoung Seop
Abstract: Computational modeling is essential in the development and application of metal additive manufacturing (MAM). Most materials processed by laser or electron beam MAM exhibit a characteristic cellular structure, where the cell walls contain a higher dislocation density than the cell interior. This kind of structure is believed to be responsible for the enhanced properties of structural members produced by MAM. In this study, a constitutive description of MAM materials was developed to accurately simulate their mechanical response to loading. The modeling frame was given by the dislocation density evolution, with two distinctly different dislocation densities being considered: those in cell walls and cell interiors considered as two separate 'phases' of the material. By employing the constitutive model developed, numerical analyses were conducted for a broad range of MAM materials - from pure metals to alloys. A comparison of the numerical simulations with experimental data for Cu and Cu-Sn from literature demonstrated that the model provides an adequate description of its uniaxial tensile properties and the dislocation density variation. In particular, the influence of the dimensions of the cellular structure and the applied strain rate is accounted for faithfully. It is suggested that the model is applicable to a broader range of MAM-processed materials as well. Graphical abstract: Image, graphical abstract